La construcción del refugio en la narrativa argentina del siglo XXI - Liliana Tozzi (Studia Romanica Posnaniensia)
Much of the Argentine narrative of the 21st century refracts the social context, determined by capitalism and its consequences in terms of exclusion, precariousness, individualism, among others. In this framework, space and temporality are related, in some cases, to processes of isolation and self-destruction of the characters; in others, to the possibility of marginal communities which resist the impositions of the hegemonic system. In this communication, I propose the idea of refuge, as a crossing point for several theoretical categories: the image of “house/home” as a place of safety (Bachelard, 2000) and home as “chronotope of intimacy” (Arfuch, 2014). The novels construct a space that includes the historical dimension of the 21st century, through a critical vision of the hegemonic system. I will tackle these lines of analysis in Mal de época, by María Sonia Cristoff, and Una música, by Hernán Ronsino.